THE IMPLEMENTATION OF CLINICAL SUPERVISION TO IMPROVE THE ABILITY OF TEACHERS IN MANAGING LEARNING PROCESS AT SDN MENANGGAL 601 SURABAYA - Mohammad Samsul Hadi (LPPM STAI Muhammadiyah Probolinggo, 2021)
Supervision carried out through the PTS is group supervision, while the approach used is a collaborative approach. The purpose of this supervision is to improve the competence of lower grade teachers in planning thematic learning. Thus this study is entitled